Efectos de la irradiación sobre las seroproteínas de Bufo arenarum revelados por tests de precipitinas - Cei, José Miguel Alfredo María (1967)
Female Toads from Mendoza (Bufo arenarum) were given whole-body single exposures to X-rays. The experimented animals showed the same corporal weigth as the controls, under the same environmental conditions. Irradiations were done in the Comision National Energia Atomica, Buenos Aires, Department of Radiobiology, in the same periods (May-August). A range of exposures was distributed as follows: 12 toads 1000 r; 12 toads 2000 r; 8 toads 3000 r; 10 toads 4000 t; 10 toads 6000 r; 10 toads 8000 r. Turbidimetric precipitin test by the Libby’s procedure were employed, at the 5 days after irradiation. Results of the tests were plotted in graphs and their statistical significance was analyzed by the current methods. Exposures of 1000 r. caused no significant alterations in the serological properties of the plasma of Toads. Doses of 2000 r and 3000-4000 r caused significant changes aboveall in globulins. Exposures of 6000-8000 r induce quantitative alterations of the plasmatic serological properties of the whole globulins and albumins. Comparison with analogous researches in other Vertebrates (Birds) was carried out.